Comparing mortality risk of patients with acute hip fractures admitted to a major trauma centre on a weekday or weekend - Rajpal Nandra (Nature Portfolio, 2017)
Abstract Proximal femoral fractures are a major public health concern with estimated annual direct and social costs amounting to £2 billion and average 30-day mortality risk of 7.5%. In response to the recent debate over out-of-hours hospital provision we investigated the ‘weekend effect’ at a major trauma centre, caring for acute injuries. A single centre, multi-surgeon review of 2060 patients performed. The distribution of patient and treatment variables compared in patients admitted on a weekday or the weekend. Fewer patients met performance indicators during weekend admission, time to surgery (63 vs. 71%) and time to geriatric review (86 vs. 91%). Weekend admission 30-day mortality was marginally lower than weekday (9.7% vs. 10.2%, OR 0.94, 95% CI 0.67 to 1.32, p = 0.7383). Increasing age, female gender, co-morbidities and confusion increased mortality risk. Binary regression analysis including these variables found no significant ‘weekend effect’. Despite the unit observing an increasing workload in the last five years, with meticulous workforce planning, senior doctor provisions and careful use of resources, it is possible to provide a seven-day fracture neck of femur service with no variation in thirty-day mortality by the day of admission.